2023
DOI: 10.1002/mco2.306
|View full text |Cite
|
Sign up to set email alerts
|

Targeting KAT2A inhibits inflammatory macrophage activation and rheumatoid arthritis through epigenetic and metabolic reprogramming

Abstract: Epigenetic regulation of inflammatory macrophages governs inflammation initiation and resolution in the pathogenesis of rheumatoid arthritis (RA). Nevertheless, the mechanisms underlying macrophage‐mediated arthritis injuries remain largely obscure. Here, we found that increased expression of lysine acetyltransferase 2A (KAT2A) in synovial tissues was closely correlated with inflammatory joint immunopathology in both RA patients and experimental arthritis mice. Administration of MB‐3, the KAT2A‐specific chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Nrf2 activation facilitates metabolic reprogramming and mitochondrial fusion, leading to a suppressed inflammatory response [ 32 ]. Zhang et al indicated that expression of lysine acetyltransferase 2A (KAT2A) in macrophages suppressed Nrf2 activity, resulting in an increased inflammatory response and bone destruction in rheumatoid arthritis [ 33 ]. The metabolism of BMSCs can also be remodeled to finetune their functions.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 activation facilitates metabolic reprogramming and mitochondrial fusion, leading to a suppressed inflammatory response [ 32 ]. Zhang et al indicated that expression of lysine acetyltransferase 2A (KAT2A) in macrophages suppressed Nrf2 activity, resulting in an increased inflammatory response and bone destruction in rheumatoid arthritis [ 33 ]. The metabolism of BMSCs can also be remodeled to finetune their functions.…”
Section: Discussionmentioning
confidence: 99%
“…With the clarification of epigenetic mechanisms in RA, key enzymes that regulate important biological processes such as DNA methylation, RNA m 6 A, and histone modification might become potential therapeutic targets for RA. The functions of azacitidine targeted for DNMT, 189 anacardic acid and MB‐3 targeted for HAT, 96 , 190 GSK‐J4 targeted for KDM, 191 MS‐275 targeted for HDAC, 192 I‐BET151 targeted for BRD4 193 have been verified in animal studies.…”
Section: Emerging Therapiesmentioning
confidence: 94%
“…Our previous research elucidated that KAT2A was overexpressed in RA synovium, and pharmacological inhibition of KAT2A significantly alleviated inflammation in collagen‐induced arthritis (CIA) mice. 96 …”
Section: Pathogenesis Of Ramentioning
confidence: 99%
“…This correlation is attributed to the promotion of Il1b and Nlrp3 transcription through histone H3K9ac modification and the inhibition of NRF2 transcription repressor activity by KAT2A. Additionally, another type of HAT, CBP/p300, enhances cytokine expression by increasing the levels of H3K27a ( 34 ). Another type of HAT, known as CBP/p300, facilitates the expression of cytokines by upregulating the abundance of H3K27ac ( 35 ).…”
Section: Different Types Of Histone Modifications and Its Functionmentioning
confidence: 99%